PENGARUH EFEKTIVITAS DEWAN KOMISARIS, DAN KOMITE AUDIT, STRUKTUR KEPEMILIKAN PERUSAHAAN, DAN KUALITAS AUDIT TERHADAP PERATAAN LABA - Achmad Junaedi; Khoirina Farina (Jurnal Manajemen Bisnis Krisnadwipayana, 2017)
This study aims to determine the effect of the effectiveness of the role of board of directors, and audit committees, corporate ownership structure and quality audits of income smoothing practices. To identify companies that practice income smoothing using Eckel Index (Eckel, 1981). The effectiveness of the board of directors and audit committee was measured using a score based on the characteristics of independence, activity, number of members and competence (Herman, 2009). The hypothesis was tested using logistic regression study sample consisted of 125 companies listed in the Indonesia Stock Exchange in 2011. The results show a company owned and controlled by the family have a higher probability to perform income smoothing practices and companies owned by foreigners has more probability low for income smoothing practices. While the effectiveness of the board of directors and audit committee does not influence the practice of smoothing earnings